Karakteristik Petani Dan Hubungannya Dengan Kompetensi Petani Lahan Sempit (Kasus : Di Desa Sinar Sari Kecamatan Dramaga Kab. Bogor Jawa Barat) - Ira Manyamsari; Mujiburrahmad Mujiburrahmad (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
ABSTRACK. The success of small farming is highly dependent on the competence of farmers as the main organizer. Competence-related characteristics such as level of education of farmers, training and business experience, interaction with FEA, the use of communication media and land area. The purpose of the study are: (1) Identify competencies smallholders in agribusiness management, and (2) analyze the relationship between the characteristics of smallholders with own competence. The research was conducted in Desa Sinar Sari Kecamatan Dramaga, Kabupaten Bogor. The approach used is a quantitative approach that is supported by qualitative data. Methods of data collection is done by observation and FGD. The population was smallholders who have less than 0.5 hectares of land. Population is taken from smallholders who are members of Gapoktan Tani Mandiri. The analysis is used to examine the relationship between the dependent variable is the independent variable by using correlation analysis Kendall W. The results explain: (1) Field of competence controlled by smallholders are in the category of very competent is: Combination branches of business, entrepreneurial spirit, harvest , and marketing efforts. Competence of postharvest handling is competent. Generally, farmers have competent competency categories. (2) The characteristics significantly related to the competence of farmers that are formal education, land and utilization of information media. Meanwhile Age, Training, Experience seeks farmer, and interaction with the instructor did not correlate significantly.